Isotherm Curve Model of Ciherang and Ciliwung Grain Varieties - Yuni, Rahmawati; Junaedi, Muhidong; Haerani, Haerani (Salaga Journal, 2025)
The advancement of post-harvest technology in Indonesia has provided accurate models for predicting grain behavior during storage. This study aimed to determine the best sorption isotherm model for describing the equilibrium moisture content of Ciherang and Ciliwung rice varieties. Rice samples were stored in 18 desiccators containing salt solutions with relative humidity (RH) levels of 10–80% at temperatures of 30, 40, and 50°C. Water content parameters were measured and three models (Oswin, Kuhn, and Chung-Pfost) were evaluated based on their coefficient of determination (R²). The results indicated that the Chung-Pfost model yielded the highest R² values for both varieties. For Ciherang, the R² values were 0.921 (30°C), 0.938 (40°C), and 0.931 (50°C), while Ciliwung showed R² values of 0.894 (30°C), 0.915 (40°C), and 0.920 (50°C). The study concluded that the Chung-Pfost model effectively represents water absorption behavior in these rice varieties, with higher temperatures reducing the equilibrium moisture content